Application of organoids in drug screening of gynecological malignant tumors - JIANG Yuanyuan, WEI Wenfei, WU Jingya, LI Huawen (Zhongguo aizheng zazhi)
Gynecologic malignant tumors are among the leading diseases threatening women’s lives and health, with the highest morbidity and mortality rates among all female diseases. These tumors originate from female reproductive organs and are typically classified based on the affected site. Ovarian cancer (OC), endometrial cancer (EC) and cervical cancer (CCA) are the most common types. Currently, gynecologic malignant tumors are primarily treated with a combination of surgery, chemotherapy and radiotherapy, where drugs play a critical role in the treatment process. However, the actual clinical effectiveness is often influenced by various factors, such as adverse reactions due to drug toxicity and the drug resistance and insensitivity observed in some patients, which limit improvements in patient survival rates. Recent studies have shown that the same type of tumor exhibits significant biological characteristics and drug response heterogeneity among different individuals, which is a key factor contributing to the varied clinical outcomes when using the same drug treatment for the same type of gynecologic malignant tumor. To achieve individualized and precise treatment for gynecologic malignant tumors, there is an urgent need to develop in vitro models that closely resemble human tumors for clinical research. Drug screening is a technique used to identify and evaluate compounds with pharmacological activity and potential therapeutic effects, providing doctors with scientific guidance on drug use, thereby avoiding blind drug testing and reducing patients' therapeutic pain and economic burden by assessing the effects of different drugs under specific conditions. Organoid models have been extensively studied as an innovative drug screening tool and personalized medicine for treating gynecologic malignancies. Organoids are tissue-like structures with a specific spatial arrangement formed in vitro through three-dimensional cell culture, capable of highly simulating the structure and function of tissues in vivo and displaying histological and genotypic characteristics very similar to human organs. This approach has largely overcome the limitations of traditional tumor models, such as patient-derived cancer cell models and patient-derived tumor xenograft models, becoming an essential research tool in oncology. It provides a more physiologically relevant experimental platform for drug screening studies of gynecologic malignancies. This paper compared the advantages and disadvantages of several preclinical cancer models, reviewed the development process of organoids, and described the establishment of gynecologic oncology organoids and their application in drug screening for ovarian, endometrial, and cervical cancers. Additionally, we discussed the current limitations of organoid technology in its application and envisioned its future development, aiming to provide insights for future medical research, particularly in new drug discovery and personalized medicine.